Biochar-Compost Interactions as Affected by Weathering: Effects on Biological Stability and Plant Growth - Aubertin, Marie-Liesse; Girardin, Cyril; Houot, Sabine; Nobile, Cécile; Houben, David; Bena, Sarah; Brech, Yann Le; Rumpel, Cornelia (Agronomy (Basel), 2021)
Biochar addition to compost is of growing interest as soil amendment. However, little is known about the evolution of material properties of biochar-compost mixtures and their effect on plants after exposure to physical weathering. This study aimed to investigate the physico-chemical characteristics of fresh and weathered biochar-compost mixtures, their biological stability and their effect on ryegrass growth. To this end, we used the contrasting stable isotope signatures of biochar and compost to follow their behavior in biochar-compost mixtures subjected to artificial weathering during 1-year of incubation. We assessed their impact on ryegrass growth during a 4-week greenhouse pot experiment. Weathering treatment resulted in strong leaching of labile compounds. However, biochar-compost interactions led to reduced mass loss and fixed carbon retention during weathering of mixtures. Moreover, weathering increased carbon mineralization of biochar-compost mixtures, probably due to the protection of labile compounds from compost within biochar structure, as well as leaching of labile biochar compounds inhibiting microbial activity. After soil application, weathered mixtures could have positive effects on biomass production. We conclude that biochar-compost interactions on soil microbial activity and plant growth are evolving after physical weathering depending on biochar production conditions.